PENGAWASAN DAN PEMBINAAN MINUMAN BERALKOHOL BERDASARKAN PERATURAN WALIKOTA MEDAN NOMOR 12 TAHUN 2011 TENTANG PELAKSANAAN PERATURAN DAERAH KOTA MEDAN NOMOR 15 TAHUN 1998 TENTANG RETRIBUSI IZIN TEMPAT PENJUALAN MINUMAN BERALKOHOL - Tri Afandy; mukhlis m; T saifullah (Fakultas Hukum Universitas Malikussaleh, 2022)
The widespread circulation of alcoholic beverage sales locations in the city of Medan is the focus of this research. Locations for selling alcoholic beverages can be found in wholesalers which are not in accordance with the Regulation of the Mayor of Medan Number 12 of 2011 concerning the Implementation of the Regional Regulation of the City of Medan Number 15 of 1998 concerning Retribution for Permits for the Sales of Alcoholic Beverages which stipulates that places where alcoholic beverages are sold 3 (three) star to 5 (five) star, bars, pubs, nightclubs and prohibition of places where alcoholic drinks are sold less than 100 m from hospitals, places of worship, and government offices. This study aims to identify and explain the Supervision and Guidance of Alcoholic Beverages Based on the Regulation of the Mayor of Medan Number 12 of 2011 and to identify and explain the barriers and weaknesses to the development and supervision of alcoholic beverages. The method that the researcher uses is the empirical juridical method with qualitative analysis. The data were obtained through library research activities and field research. Data analysis was carried out from the beginning and continued throughout the research process, namely data collection, data reduction, data assessment and drawing conclusions. Based on the results of the study, it is known that the Guidance and Supervision of Alcoholic Drinks based on Medan Mayor Regulation Number 12 of 2011 carried out by the Integrated Team for Supervision and Control of Alcoholic Beverage Circulation (TP3MB) has not been maximized because there are still findings of illegal drink sellers but TP3MB has made efforts to Controlling alcoholic bever5ages, including monitoring the sale of alcoholic beverages and providing guidance to sellers of alcoholic beverages who have obtained permits. There are also obstacles and weaknesses experienced by the industry and trade offices, namely the lack of personnel in supervising alcoholic beverage sellers and the difficulty in obtaining responses from business actors. carry out supervision and guidance on alcoholic beverages.